Detection of coronaviruses in Pteropus & Rousettus species of bats from different States of India - Yadav, Pragya; Shete-Aich, Anita; Nyayanit, Dimpal; Pardeshi, Prachi; Majumdar, Triparna; Balasubramanian, R; Ullas, Padinjaremattathil; Mohandas, Sreelekshmy; Dighe, Hitesh; Sawant, Pradeep; Patil, Savita; Patil, Dilip; et al. (Indian journal of medical research (New Delhi, India : 1994), 2020)
Background & objectives: Bats are considered to be the natural reservoir for many viruses, of which some are potential human pathogens. In India, an association of Pteropus medius bats with the Nipah virus was reported in the past. It is suspected that the recently emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) also has its association with bats. To assess the presence of CoVs in bats, we performed identification and characterization of bat CoV (BtCoV) in P. medius and Rousettus species from representative States in India, collected during 2018 and 2019. Methods: Representative rectal swab (RS) and throat swab specimens of Pteropus and Rousettus spp. bats were screened for CoVs using a pan-CoV reverse transcription-polymerase chain reaction (RT-PCR) targeting the RNA-dependent RNA polymerase (RdRp) gene. A single-step RT-PCR was performed on the RNA extracted from the bat specimens. Next-generation sequencing (NGS) was performed on a few representative bat specimens that were tested positive. Phylogenetic analysis was carried out on the partial sequences of RdRp gene sequences retrieved from both the bat species and complete viral genomes recovered from Rousettus spp. Results: Bat samples from the seven States were screened, and the RS specimens of eight Rousettus spp. and 21 Pteropus spp. were found positive for CoV RdRp gene. Among these, by Sanger sequencing, partial RdRp sequences could be retrieved from three Rousettus and eight Pteropus bat specimens. Phylogenetic analysis of the partial RdRp region demonstrated distinct subclustering of the BtCoV sequences retrieved from these Rousettus and Pteropus spp. bats. NGS led to the recovery of four sequences covering approximately 94.3 per cent of the whole genome of the BtCoVs from Rousettus bats. Three BtCoV sequences had 93.69 per cent identity to CoV BtRt-BetaCoV/GX2018. The fourth BtCoV sequence was 96.8 per cent identical to BtCoV HKU9-1. Interpretation & conclusions: This study was a step towards understanding the CoV circulation in Indian bats. Detection of potentially pathogenic CoVs in Indian bats stresses the need for enhanced screening for novel viruses in them. One Health approach with collaborative activities by the animal health and human health sectors in these surveillance activities shall be of use to public health. This would help in the development of diagnostic assays for novel viruses with outbreak potential and be useful in disease interventions. Proactive surveillance remains crucial for identifying the emerging novel viruses with epidemic potential and measures for risk mitigation.